Understanding the journey : a lifespan approach to working with grieving people - Glazer, Hilda R.; Clark-Foster, Myra (Charles C Thomas, Publisher, Ltd., 2019)
The death of a loved one is a traumatic event for both adults and children. Grieving has no rules, no prescribed course, or expiration date. After a death, the feelings and experiences that follow can be extremely overwhelming and confusing. The authors of this book create a supportive environment that normalizes the phases of grief through clinical expertise, including a lifespan approach that indicates grief is certainly a journey from which none of us ever escapes nor perhaps reaches closure. This book will be a significant resource for mental health professionals, grief counselors, human.